Effect of visit-to-visit blood pressure variability on cardiovascular events in populations with different body mass indexes: a prospective cohort study - Shouling Wu; Haojia Chen; Youren Chen; Weiqiang Wu; Jianhuan Huang; Zekai Chen; Zhichao Chen; Xiuzhu Yan (BMJ Open)
Objective This study was performed to explore the effects of visit-to-visit blood pressure variability (BPV) on cardiovascular events (CVEs) in people with various body mass indexes (BMIs).Design Prospective cohort study.Setting The average real variability of systolic blood pressure (ARVSBP) was the indicator for visit-to-visit BPV. The participants were divided into three groups: normal weight, overweight and obesity. We further divided these groups into four subgroups based on the ARVSBP. A Cox regression model was used to calculate the HRs of the ARVSBP on CVEs in the same and different BMI groups. Additionally, a competitive risk model was used to calculate the HRs of the ARVSBP on CVEs in the same BMI group.Participants In total, 41 043 individuals met the inclusion criteria (no historical CVEs or tumours, no incidence of CVEs or tumours and no death during the four examinations) and had complete systolic blood pressure and BMI data.Results A total of 868 CVEs occurred. The cumulative incidence of CVEs increased as ARVSBP rose in both the normal weight and overweight groups. In same BMI groups, the risk of CVEs significantly increased as ARVSBP increased only in the normal weight group (highest quartiles of ARVSBP: HR (95% CI) 2.20 (1.46–3.31)). In the different BMI groups, the risk of CVEs in the ARVSBP subgroup in each BMI group was higher than that the least quintile of ARVSBP in the normal weight group (highest quartiles of ARVSBP in obesity: HR (95% CI) 2.28 (1.47–3.55)). The result of the competitive risk model did not change.Conclusions As BMI and ARVSBP increase, the risk of CVEs increases. However, the risk of visit-to-visit BPV on CVEs varies in different BMI groups, especially in people of normal weight.Trial registration number CHiCTR-TNC1100 1489.